Does opercular shortening influence seaward migration success of stocked Atlantic salmon (Salmo salar) smolts? - Martin H. Larsen; Kim Birnie-Gauvin; Henrik Baktoft; Søren T. Thomassen; Kim Aarestrup (Fisheries Research, 2026)

Do offspring characteristics reflect parental migration variation? - Madeleine Berry; Jan G. Davidsen; Marie Nevoux; Kim Aarestrup; Carlos M. Alexandre; Sara S. Silva; Alexander Thorén; Anders Engstöm; Matilda Ahvenainen; Johan Höjesjö (Journal of Fish Biology, 2026)
Sea trout, Salmo trutta , display a wide range of migratory behaviours, and one aspect of variation comes from freshwater migration distance. The overall aim of this study was to determine if offspring of long‐ and short‐distance migrants exhibited phenotypic differences relating to parental migration distance. For that purpose, we conducted several behavioural tests (dyadic contest, boldness scoring and open field test) and morphological analysis (relative pectoral‐fin length) in multiple freshwater systems across the distribution range of the target species in Europe. It was expected that offspring of long‐distance migrants would be more active, bold and dominant than those of short‐distance migrants and would have longer pectoral fins relative to body length. Additionally, we investigated if boldness varied in relation to latitude. We showed that offspring of long‐distance migrants were more dominant in two cases and more active in one case than those of short‐distance migrants; however, there was no difference in swimming distance or velocity. Boldness and relative pectoral‐fin length were significantly related to site of origin; however, the direction of this relationship differed between systems. Generally, we detected a decrease in boldness with declining latitude. In summary, we have detected variation among juveniles related to location within a stream; however, the drivers and processes behind these are likely more complex than purely parental migratory strategy. Our results can inform suitable management and conservation efforts directed to anadromous Salmo trutta . For example, habitat restoration and removal of migration barriers can increase the possible range of migration distances helping maintain the phenotypic diversity of offspring.

Cold environment influences on diel vertical migration of silver-phase Japanese eels in the Kuroshio-Oyashio confluence region - Takatoshi Higuchi; Shun Watanabe; Ryotaro Manabe; Michael J. Miller; Kim Aarestrup; Jun Aoyama; Eric Feunteun; Katsumi Tsukamoto (Environmental Biology of Fishes, 2025)

Revealing the oceanic spawning migrations of Australian long-finned eels (Anguilla reinhardtii) via satellite telemetry - Wayne M. Koster; Håkan Westerberg; David Dawson; Roland Kahsnitz; Kim Aarestrup; Ben Fanson (Frontiers in Marine Science, 2025)
This study presents the first investigation into the oceanic spawning migrations of Australian long-finned eels ( Anguilla reinhardtii ), a critical and previously undocumented stage in their life cycle. In autumn 2024, twenty adult eels were collected from two estuaries in southern Australia and tagged with pop-up satellite archival tags. Individuals were successfully tracked up to five months, with some migrating as far as ~2,500 km from their release sites to the tropical Coral Sea. Migration trajectories revealed relatively consistent and direct movement pathways, with eels remaining several hundred kilometers offshore for much of their journey before venturing farther offshore during later stages. Tag data provided clear evidence of predation events, indicating that escapement to the sea does not guarantee successful spawning and highlighting the potential ecological role of eels within marine food webs. Approximately 40% of migrations were prematurely terminated due to predation, with sharks likely responsible in nearshore environments and marine mammals in offshore regions. Additionally, consistent observations of diel vertical migration, characterized by nocturnal ascents toward the surface and diurnal descents to deeper waters, offer valuable insights into behavioral adaptations during the oceanic migration phase of this enigmatic life history. Tag endpoints and reconstructed migratory trajectories generally aligned with a region between the East Australian Current and the Lord Howe Seamount Chain. Several endpoints clustered within a small region of the northeastern Coral Sea, south of the Solomon Islands. These locations align with historical leptocephali collection sites, strengthening the hypothesis that the spawning area of long-finned eels lies in the northeastern Coral Sea.

New trophic insights associated with the return of a top predator, bluefin tuna, to Skagerrak and the Sound - Gustav Hellström; Kim Birnie-Gauvin; Petter Lundberg; William Jaktén Langert; Kristi Källo; Lene K. Sortland; Brian R. MacKenzie; Jose Luis Varela; Anders Koed; Einar Eg Nielsen; Andreas Sundelöf; Hege Sande; et al. (Fisheries Research, 2025)

A Physical Bottleneck Increases Predation on Atlantic Salmon Smolts During Seaward Migration in an Irish Index River - Lene Klubben Sortland; Glen Wightman; Hugo Flávio; Kim Aarestrup; William Roche (Fisheries Management and Ecology, 2025)
Counting departing smolts and returning adults in index rivers is essential to estimate marine survival and track population trends of Atlantic salmon ( Salmo salar ). However, mortalities between counting facilities and a river mouth can skew survival estimates. We used acoustic and radio telemetry to investigate survival, mortality sources and behaviour of wild salmon smolts in the River Erriff, Ireland's index river, and Killary Fjord. Smolts were tagged with acoustic tags in 2017 ( n = 40) and 2018 ( n = 35) and radio tags in 2018 ( n = 30). Survival was low for acoustic‐tagged smolts in 2017 (26%) and 2018 (47%), mainly due to riverine mortality. Terrestrial or avian predators consumed 65% of acoustic‐tagged smolts in 2017 and 67% of radio‐tagged smolts in 2018. Nocturnal migration and ebb tide transportation likely contributed to high estuary survival. High predation on smolts emphasised the importance of assessing freshwater mortality for effective salmon management.

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

Comparing the migration behavior and survival of Atlantic salmon ( Salmo salar ) and brown trout ( Salmo trutta ) smolts - Lene Klubben Sortland; Kim Aarestrup; Kim Birnie‐Gauvin (Journal of Fish Biology, 2025)
Many organisms rely on migrations between habitats to maximize lifetime fitness, but these migrations can be risky due to a suite of factors. In anadromous salmonids, the smolt migration from fresh water to sea is a critical life stage, during which smolts can experience high mortality from multiple sources. This study investigated the migratory behavior and survival of Atlantic salmon ( Salmo salar ) and anadromous brown trout ( Salmo trutta ) smolts during their seaward migration using acoustic telemetry between March and May 2021. Due to the extinction of wild salmon in the River Gudenaa after the construction of the Tange hydropower plant, this study used hatchery‐reared salmon originating from a nearby Danish river. A total of 75 hatchery‐reared salmon smolts, 75 hatchery‐reared trout smolts, and 75 wild trout smolts were tagged with acoustic transmitters and released into River Gudenaa, Denmark. The downstream movements of tagged fish were monitored using acoustic receivers deployed in the river and fjord. Hatchery‐reared trout initiated migration first, followed by hatchery‐reared salmon, with wild trout being the last to migrate. There was no difference in riverine progression rates among the three smolt groups, but noticeable differences emerged once in the fjord: trout (wild and hatchery) slowed down, whereas hatchery‐reared salmon maintained their speed. Riverine migration was predominantly nocturnal for all smolts; however, daytime migration increased at the fjord arrays. Day‐of‐year significantly influenced diurnal patterns in the river and fjord, where daytime migration increased later in the year. Hatchery‐reared salmon and wild trout had reasonably good overall survival from river to sea entry (≥66%), whereas hatchery‐reared trout had poor survival (c.26%). The fjord was the major bottleneck for survival of hatchery‐reared trout. We found no strong evidence for differences in progression rate or diurnal patterns between wild and hatchery‐reared trout to explain the lower survival. This study demonstrates that salmon and trout differ in their life‐history strategy already in the post‐smolt phase, and that stocking is a sub‐optimal strategy to aid wild populations.

Tracking aquatic animals for fisheries management in European waters - Aytaç Özgül; Kim Birnie‐Gauvin; David Abecasis; Josep Alós; Kim Aarestrup; Jan Reubens; Jon Bolland; Altan Lök; Jena E. Edwards; Polona Pengal; Marie Prchalová; Milan Říha; et al. (Fisheries Management and Ecology, 2024)
Acoustic telemetry (AT) has emerged as a valuable tool for monitoring aquatic animals in both European inland and marine waters over the past two decades. The European Tracking Network (ETN) initiative has played a pivotal role in promoting collaboration among AT researchers in Europe and has led to a significant increase in the number of tagged and observed aquatic animals in transboundary European waters. While AT benefits decision‐making and delivers essential data to management bodies, its potential for management decision‐making mechanisms has yet to be fully harnessed. We reviewed existing research, studies, and organisational initiatives related to aquatic animal tracking and their utility in fisheries management in European waters. We found that AT has already contributed to many aspects of fisheries management, such as improved understanding of stock dynamics, identification of critical habitats, assessment of migration routes, and evaluation of the effectiveness of conservation measures. However, broader utilisation of tracking technologies is needed. By leveraging the full potential of AT, managers can make more informed decisions to protect, restore, and sustainably manage European waters and creatures that live therein.

Evidence of marine predation on silver New Zealand longfin eels, Anguilla dieffenbachii - Donald Jellyman; Paul Franklin; Kim Aarestrup; Kim Birnie‐Gauvin; Cindy Baker; Phillip Jellyman (Fisheries Management and Ecology, 2024)
The use of Pop‐up Satellite Archival Tags (PSATs) has provided considerable new information about the behaviour of migrating (silver) eels ( Anguilla spp.) at sea, with 9 of 19 recognised species or subspecies tagged to date. However, such studies often reported premature tag detachment and relatively high rates of predation. Since 2000, several PSAT‐tagged New Zealand longfin eels, Anguilla dieffenbachii , were released to understand migratory behaviour and location of potential spawning grounds. Of 20 PSAT‐tagged eels released in 2019, all tags detached prematurely, but 7 (58%) were likely eaten or injured by predators 1–81 days after release. Two eels were probably eaten by sperm whales, whereas other tagged eels were likely eaten by lamniform and non‐lamniform sharks, and southern bluefin tuna. Because of the high rate of predation, we recommend that future releases should be from smaller catchments or offshore.

Anthropogenic Contaminants Shape the Fitness of the Endangered European Eel: A Machine Learning Approach - Bastien Bourillon; Eric Feunteun; Anthony Acou; Thomas Trancart; Nils Teichert; Claude Belpaire; Sylvie Dufour; Paco Bustamante; Kim Aarestrup; Alan Walker; David Righton (Fishes, 2022)
European eel is thought to be a symbol of the effects of global change on aquatic biodiversity. The species has persisted for millions of years and faced drastic environmental fluctuations thanks to its phenotypic plasticity. However, the species has recently declined to historically low levels under synergistic human pressures. Sublethal chemical contamination has been shown to alter reproductive capacity, but the impacts and required actions are not fully addressed by conservation plans. This paper proposes a modelling approach to quantify the effects of sublethal contamination by anthropogenic pollutants on the expression of life history traits and related fitness of the critically endangered European eel. Material and Methods: We sampled female silver eels from eight different catchments across Europe previously shown to be representative of the spectrum of environmental variability and contamination. We measured 11 fitness-related life history traits within four main categories: fecundity, adaptability and plasticity, migratory readiness, and spawning potential. We used machine learning in models to explore the phenotypic reaction (expression of these life history traits) according to geographical parameters, parasite burdens (the introduced nematode Anguillicoloides crassus) and anthropogenic contaminants (persistent organic pollutants (POPs) in muscular tissue and trace elements (TEs) in gonads, livers and muscles). Finally, we simulated, the effects of two management scenarios—contamination reduction and contamination increase—on the fecundity and recruitment. Results: Contamination in our sampling was shown to have a stronger control on life history traits than do geographic and environmental factors that are currently described in the literature. We modelled different contamination scenarios to assess the benefit of mitigation: these scenarios suggest that reducing pollutants concentrations to the lowest values that occurred in our sampling design would double the fecundity of eels compared to the current situation. Discussion: Remediation of contamination could represent a viable management option for increasing the resilience of eel populations, with much more effects than solely reducing fishing mortality. More broadly, our work provides an innovative way for quantitative assessment of the reaction norms of species’ biological traits and related fecundity to contamination by organic and inorganic pollutions thus opening new management and conservation pathways to revert the erosion of biodiversity.

Toward a decade of ocean science for sustainable development through acoustic animal tracking - Josep Alós; Kim Aarestrup; David Abecasis; Pedro Afonso; Alexandre Alonso‐Fernandez; Eneko Aspillaga; Margarida Barcelo‐Serra; Jonathan Bolland; Miguel Cabanellas‐Reboredo; Robert Lennox; Ross McGill; Aytaç Özgül; et al. (Global Change Biology, 2022)
The ocean is a key component of the Earth's dynamics, providing a great variety of ecosystem services to humans. Yet, human activities are globally changing its structure and major components, including marine biodiversity. In this context, the United Nations has proclaimed a Decade of Ocean Science for Sustainable Development to tackle the scientific challenges necessary for a sustainable use of the ocean by means of the Sustainable Development Goal 14 (SDG14). Here, we review how Acoustic animal Tracking, a widely distributed methodology of tracking marine biodiversity with electronic devices, can provide a roadmap for implementing the major Actions to achieve the SDG14. We show that acoustic tracking can be used to reduce and monitor the effects of marine pollution including noise, light, and plastic pollution. Acoustic tracking can be effectively used to monitor the responses of marine biodiversity to human‐made infrastructures and habitat restoration, as well as to determine the effects of hypoxia, ocean warming, and acidification. Acoustic tracking has been historically used to inform fisheries management, the design of marine protected areas, and the detection of essential habitats, rendering this technique particularly attractive to achieve the sustainable fishing and spatial protection target goals of the SDG14. Finally, acoustic tracking can contribute to end illegal, unreported, and unregulated fishing by providing tools to monitor marine biodiversity against poachers and promote the development of Small Islands Developing States and developing countries. To fully benefit from acoustic tracking supporting the SDG14 Targets, trans‐boundary collaborative efforts through tracking networks are required to promote ocean information sharing and ocean literacy. We therefore propose acoustic tracking and tracking networks as relevant contributors to tackle the scientific challenges that are necessary for a sustainable use of the ocean promoted by the United Nations.

Important questions to progress science and sustainable management of anguillid eels - David Righton; Adam Piper; Kim Aarestrup; Elsa Amilhat; Claude Belpaire; John Casselman; Martin Castonguay; Estibaliz Díaz; Hendrik Dörner; Elisabeth Faliex; Eric Feunteun; Nobuto Fukuda; et al. (Fish and Fisheries, 2021)
Anguillid eels are found globally in fresh, transitional and saline waters and have played an important role in human life for centuries. The population status of several species is now of significant concern. The threats to populations include direct exploitation at different life stages, blockages to migratory routes by dams and other structures, changes in river basin management that impact habitat carrying capacity and suitability, pollution, climate change, diseases and parasites. While much has been done to understand eel biology and ecology, a major challenge is to identify the key research and management questions so that effective and targeted studies can be designed to inform conservation, management and policy. We gathered 30 experts in the field of eel biology and management to review the current state of knowledge for anguillid eel species and to identify the main topics for research. The identified research topics fell into three themes: (a) Lifecycle and Biology; (b) Impacts and (c) Management. Although tropical anguillid eels are by far the least well understood, significant knowledge gaps exist for all species. Considerable progress has been made in the last 20 years, but the status of many species remains of great concern, particularly for northern temperate species. Without improved engagement and coordination at the regional, national and international level, the situation is unlikely to improve. Further, adaptive management mechanisms to respond to developments in science, policy and our knowledge of potential threats are required to ensure the future of these important and enigmatic species.

Marine mortality in the river? Atlantic salmon smolts under high predation pressure in the last kilometres of a river monitored for stock assessment - Hugo Flávio; Richard Kennedy; Dennis Ensing; Niels Jepsen; Kim Aarestrup (Fisheries Management and Ecology, 2020)
The River Bush (Northern Ireland) is an index river for the estimation of Atlantic salmon, Salmo salar L., stock size, population dynamics and marine survival rates. Marine survival estimates are based on the number of smolts counted at a trap 3.5 km upstream of the river outlet. The survival from release to coastal inshore waters for acoustic‐tagged smolts released at the Bushmills trap varied between 32% and 68%, with both year and brightness during river exit playing a significant role in explaining the variations in survival. This constitutes an important survival bottleneck. Contrary to true marine mortality, this significant loss of smolts in the river and nearshore environments could be reduced by focused management actions. More studies on other rivers, where smolts are enumerated above the head of tide, could further partition smolt and post‐smolt mortality, help differentiate true marine survival and help understand fluctuations in adult returns.

From endangered to sustainable: Multi‐faceted management in rivers and coasts improves Atlantic salmon ( Salmo salar ) populations in Denmark - Anders Koed; Kim Birnie‐Gauvin; Finn Sivebæk; Kim Aarestrup (Fisheries Management and Ecology, 2020)
The status of Atlantic salmon, Salmo salar L., over the last decades has been of concern across its entire distribution area. Its anadromous nature exposes the species to human pressures in both freshwater and marine environments, and over long periods, thus exacerbating its decline. Given its value within the food industry, the recreational angling community as well as culturally, the status of Atlantic salmon is regarded as a matter of national and international conservation interest, providing great incentive for its management. The literature currently lacks specific examples of successful and unsuccessful management strategies and practices for Atlantic salmon populations at a broader scale. To address this, the present article describes how the multi‐faceted management approach taken for Danish Atlantic salmon, which included changes in legislation, stocking practices, habitat restoration, population genetics and barrier removals, successfully rehabilitated salmon populations in four major Danish rivers. Specific recommendations are provided for the successful management of Atlantic salmon elsewhere.

Overlooked aspects of the Salmo salar and Salmo trutta lifecycles - Kim Birnie-Gauvin; Eva B. Thorstad; Kim Aarestrup (Reviews in Fish Biology and Fisheries, 2019)

Environmental influences on life history strategies in partially anadromous brown trout ( Salmo trutta , Salmonidae) - Marie Nevoux; Bengt Finstad; Jan Grimsrud Davidsen; Ross Finlay; Quentin Josset; Russell Poole; Johan Höjesjö; Kim Aarestrup; Lo Persson; Oula Tolvanen; Bror Jonsson (Fish and Fisheries, 2019)
This paper reviews the life history of brown trout and factors influencing decisions to migrate. Decisions that maximize fitness appear dependent on size at age. In partly anadromous populations, individuals that attain maturity at the parr stage typically become freshwater resident. For individual fish, the life history is not genetically fixed and can be modified by the previous growth history and energetic state in early life. This phenotypic plasticity may be influenced by epigenetic modifications of the genome. Thus, factors influencing survival and growth determine life‐history decisions. These are intra‐ and interspecific competition, feeding and shelter opportunities in freshwater and salt water, temperature in alternative habitats and flow conditions in running water. Male trout exhibit alternative mating strategies and can spawn as a subordinate sneaker or a dominant competitor. Females do not exhibit alternative mating behaviour. The relationship between growth, size and reproductive success differs between sexes in that females exhibit a higher tendency to migrate than males. Southern populations are sensitive to global warming. In addition, fisheries, aquaculture with increased spreading of salmon lice , introduction of new species, weirs and river regulation, poor water quality and coastal developments all threaten trout populations. The paper summarizes life‐history data from six populations across Europe and ends by presenting new research questions and directions for future research.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Artificial lakes delay the migration of brown trout Salmo trutta smolts: a comparison of migratory behaviour in a stream and through an artificial lake - Michael Schwinn; Henrik Baktoft; Kim Aarestrup; Anders Koed (Journal of Fish Biology, 2019)
Juvenile salmonids experience high mortality when negotiating lentic waters during their downstream migration to the sea. The development of artificial lakes and wetlands in streams has become a widely used management tool to reduce nutrient load to coastal areas. Such wetlands may threaten anadromous populations. In this study we quantify net ground speed of downstream migrating brown trout Salmo trutta smolts in equally long stream and lake sections in a Danish lowland stream and artificial lake. This was done by passive integrated transponder telemetry in 2016 and 2017. Mean net ground speed in the stream section was 36.58 and 0.8 km day −1 in the lake section. This decrease of net ground speed through the lake may lead to prolonged exposure to predators and probably contributes to high mortalities threatening anadromous populations.

The future of fish passage science, engineering, and practice - Ana T. Silva; Martyn C. Lucas; Theodore Castro‐Santos; Christos Katopodis; Lee J. Baumgartner; Jason D. Thiem; Kim Aarestrup; Paulo S. Pompeu; Gordon C. O'Brien; Douglas C. Braun; Nicholas J. Burnett; David Z. Zhu; et al. (Fish and Fisheries, 2018)
Much effort has been devoted to developing, constructing and refining fish passage facilities to enable target species to pass barriers on fluvial systems, and yet, fishway science, engineering and practice remain imperfect. In this review, 17 experts from different fish passage research fields (i.e., biology, ecology, physiology, ecohydraulics, engineering) and from different continents (i.e., North and South America, Europe, Africa, Australia) identified knowledge gaps and provided a roadmap for research priorities and technical developments. Once dominated by an engineering‐focused approach, fishway science today involves a wide range of disciplines from fish behaviour to socioeconomics to complex modelling of passage prioritization options in river networks. River barrier impacts on fish migration and dispersal are currently better understood than historically, but basic ecological knowledge underpinning the need for effective fish passage in many regions of the world, including in biodiversity hotspots (e.g., equatorial Africa, South‐East Asia), remains largely unknown. Designing efficient fishways, with minimal passage delay and post‐passage impacts, requires adaptive management and continued innovation. While the use of fishways in river restoration demands a transition towards fish passage at the community scale, advances in selective fishways are also needed to manage invasive fish colonization. Because of the erroneous view in some literature and communities of practice that fish passage is largely a proven technology, improved international collaboration, information sharing, method standardization and multidisciplinary training are needed. Further development of regional expertise is needed in South America, Asia and Africa where hydropower dams are currently being planned and constructed.

N-acetylcysteine manipulation fails to elicit an increase in glutathione in a teleost model - Kim Birnie-Gauvin; Martin H. Larsen; Kim Aarestrup; William G. Willmore; Steven J. Cooke (Fish Physiology and Biochemistry, 2018)

If and when: intrinsic differences and environmental stressors influence migration in brown trout (Salmo trutta) - Kathryn S. Peiman; Kim Birnie-Gauvin; Jonathan D. Midwood; Martin H. Larsen; Alexander D. M. Wilson; Kim Aarestrup; Steven J. Cooke (Oecologia, 2017)

Pike (Esox lucius L.) on the edge: consistent individual movement patterns in transitional waters of the western Baltic - Lene Jacobsen; Dorte Bekkevold; Søren Berg; Niels Jepsen; Anders Koed; Kim Aarestrup; Henrik Baktoft; Christian Skov (Hydrobiologia, 2017)

Serum estrogen and SHBG levels and breast cancer incidence among users and never users of hormone replacement therapy - Anne Mette Lund Würtz; Anne Tjønneland; Jane Christensen; Lars Ove Dragsted; Julie Aarestrup; Cecilie Kyrø; Kim Overvad; Anja Olsen (Cancer Causes & Control, 2012)

Non-indigenous signal crayfish Pacifastacus leniusculus are now common in Danish streams: preliminary status for national distribution and protective actions - Christian Skov; Kim Aarestrup; Finn Sivebæk; Stig Pedersen; Trude Vrålstad; Søren Berg (Biological Invasions, 2011)

All roads lead to home: panmixia of European eel in the Sargasso Sea - THOMAS D. ALS; MICHAEL M. HANSEN; GREGORY E. MAES; MARTIN CASTONGUAY; LASSE RIEMANN; KIM AARESTRUP; PETER MUNK; HENRIK SPARHOLT; REINHOLD HANEL; LOUIS BERNATCHEZ (Molecular Ecology, 2011)
European eels ( Anguilla anguilla ) spawn in the remote Sargasso Sea in partial sympatry with American eels ( Anguilla rostrata ), and juveniles are transported more than 5000 km back to the European and North African coasts. The two species have been regarded as classic textbook examples of panmixia, each comprising a single, randomly mating population. However, several recent studies based on continental samples have found subtle, but significant, genetic differentiation, interpreted as geographical or temporal heterogeneity between samples. Moreover, European and American eels can hybridize, but hybrids have been observed almost exclusively in Iceland, suggesting hybridization in a specific region of the Sargasso Sea and subsequent nonrandom dispersal of larvae. Here, we report the first molecular population genetics study based on analysis of 21 microsatellite loci in larvae of both Atlantic eel species sampled directly in the spawning area, supplemented by analysis of European glass eel samples. Despite a clear East–West gradient in the overlapping distribution of the two species in the Sargasso Sea, we only observed a single putative hybrid, providing evidence against the hypothesis of a wide marine hybrid zone. Analyses of genetic differentiation, isolation by distance, isolation by time and assignment tests provided strong evidence for panmixia in both the Sargasso Sea and across all continental samples of European eel after accounting for the presence of sibs among newly hatched larvae. European eel has declined catastrophically, and our findings call for management of the species as a single unit, necessitating coordinated international conservation efforts.

Factors affecting the within-river spawning migration of Atlantic salmon, with emphasis on human impacts - Eva B. Thorstad; Finn Økland; Kim Aarestrup; Tor G. Heggberget (Reviews in Fish Biology and Fisheries, 2008)

Net ground speed of downstream migrating radio-tagged Atlantic salmon (Salmo salar L.) and brown trout (Salmo trutta L.) smolts in relation to environmental factors - Kim Aarestrup; Christian Nielsen; Anders Koed (Hydrobiologia, 2002)

Spawning migration of sea trout (Salmo trutta (L)) in a Danish river - Kim Aarestrup; Niels Jepsen (Hydrobiologia, 1998)

Survival of radiotagged Atlantic salmon (Salmo salar L.) – and trout (Salmo trutta L.) smolts passing a reservoir during seaward migration - Niels Jepsen; Kim Aarestrup; Finn Økland; Gorm Rasmussen (Hydrobiologia, 1998)